The Effect of Radio Broadcasting On Students' Speaking Achievement - Megasari Dewi Suryani (Language-Edu, 2020)
This study was intended toward discover the effect of radio broadcasting on students’ speaking achievement at second grade of SMP Bilingual Terpadu Krian on academic year 2019/2020. The research problem is whether the students of second grade in SMP Bilingual Terpadu Krian have higher speaking skill after taking radio broadcasting. A pre-experimental design was implemented in this study. The instrument of the test was the oral speaking test. The student of second grades became he subjects of the research at SMP Bilingual Terpadu. The data of the test which were in the form of the gained score was analyzed using a paired sample t-test with the significant level of p=5%. It was found that the pre-test mean score was 45.20667 and also the post-test mean score was 77.70833. The t-obtained value was 21.398 (p: .000). Therefore, it can be concluded that the application of radio broadcasting on students’ speaking achievement was effective.Keywords: effect, radio broadcasting, increase, speaking achievement